ISOLATED NOCTURNAL HYPERTENSION HAD HIGHER 24-HOUR URINE SODIUM/POTASSIUM RATIO THAN NORMOTENSION. (June 2018) - Rhee, M.-Y.; Kim, K.I.; Nah, D.Y.; Gu, N.; Sung, K.C.; Hong, K.S.; Cho, E.J.; Jo, S.H.
Abstract: Objective: Only few studies showed the association of salt intake with nocturnal blood pressure (BP). However, little is known about salt intake in patients with isolated nocturnal hypertension. Design and method: Among the 1128 participants, 740 participants who had complete 24-hour urine collection and valid 24-h ambulatory BP monitoring were analyzed. Participants were grouped in 4 groups: normotension (NT, n = 371), isolated daytime hypertension (IDHT, n = 26), isolated nocturnal hypertension (INHT, n = 177), and both-hypertension having both daytime and nocturnal hypertension (both-HT, n = 166). Results: The 24-hour urine sodium (24HUNa) was 155.4 ± 62.9, 164.1 ± 65.5, 169.8 ± 65.8 and 180.0 ± 72.2 mmol/24 hour, respectively. The 24-hour urine potassium (24HUK) was 56.6 ± 19.7, 51.3 ± 14.7, 60.1 ± 25.4 and 60.1 ± 21.4 mmol/24-hour and the 24-hour urine sodium/potassium ratio (24HUNa/24HUK) were 2.9 ± 1.2, 3.3 ± 1.0, 3.3 ± 3.2 and 3.2 ± 1.3, respectively. Compared to NT group, INHT had higher 24HUNa (p = 0.014), and both-HT had higher 24HUNa and 24HUNa/24HUK (p < 0.001 and 0.016, respectively). There was no difference in 24HUNa, 24HUNK and 24HUNa/24HUK between INHT and both-HT. In multivariate analysis controlled with age, gender, body mass index, estimated glomerular filtration rate, and use of diuretics, INHT showed significantly higher 24HUNa/24HUK than NT (p = 0.038). The difference of 24HUNa and 24HUNa/24HUK between NT and both-HT was not persistent in multivariate analysis. Conclusions: The result of present study suggests that high ratio of sodium/potassium intake may be a risk of isolated nocturnal hypertension.